Mapping the Future of Halal Tourism Research: Bibliometric Analysis Using VOSviewer - Marwah Qodarsyah Ramadhan Ramadhan; Kamilatus Salsabila; Rahmayati Koto (Universitas Negeri Surabaya, 2026)
Halal tourism has emerged as one of the fastest-growing segments of the global tourism industry, driven by expanding Muslim populations and increasing demand for Shariah-compliant travel services. Despite significant scholarly attention, the field lacks a systematic mapping of its intellectual landscape across major academic databases. This study employs a bibliometric analysis of 189 documents from Scopus and 956 documents from Google Scholar, retrieved using the keyword